2020
DOI: 10.1111/jcmm.15203
|View full text |Cite
|
Sign up to set email alerts
|

TRIM23 overexpression is a poor prognostic factor and contributes to carcinogenesis in colorectal cancer

Abstract: The tripartite motif (TRIM) family proteins play a great role in carcinogenesis. However, the expression pattern, prognostic value and biological functions of tripartite motif containing 23 (TRIM23) in colorectal cancer (CRC) are poorly understood. Here, we found that TRIM23 is up‐regulated and associated with tumour size, lymph node metastasis, American Joint Committee on Cancer (AJCC) stage and poor prognosis in CRC. Multivariate Cox regression analyses revealed that TRIM23 overexpression could be identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…At the same time, MDM2 is targeted by p53 to form a negative feedback loop for the dynamic regulation of p53 under stressed and unstressed conditions [177]. RCHY1, COP1, CHIP, HUWE1, RING1, FBXW7, Synoviolin, MKRN1, TOPORS, CARP1/2, CUL4a-DDB1-ROC, CUL5, RNF115, TRIM23, TRIM24, TRIM28, TRIM39, TRIM69, TRIM71 can also target p53 for K48-linked polyubiquitination and degradation [178][179][180][181][182][183][184][185]. K48linked polyubiquitination of p53 can be regulated by various molecules.…”
Section: Ubiquitination Of P53mentioning
confidence: 99%
“…At the same time, MDM2 is targeted by p53 to form a negative feedback loop for the dynamic regulation of p53 under stressed and unstressed conditions [177]. RCHY1, COP1, CHIP, HUWE1, RING1, FBXW7, Synoviolin, MKRN1, TOPORS, CARP1/2, CUL4a-DDB1-ROC, CUL5, RNF115, TRIM23, TRIM24, TRIM28, TRIM39, TRIM69, TRIM71 can also target p53 for K48-linked polyubiquitination and degradation [178][179][180][181][182][183][184][185]. K48linked polyubiquitination of p53 can be regulated by various molecules.…”
Section: Ubiquitination Of P53mentioning
confidence: 99%
“…Multiple TRIM proteins have been identified and most of them homodimerize through their coiled-coil domain [318,319]. As these proteins are overexpressed in many tumors they are hypothesized to contribute to tumorigenesis [320,321]. For instance, increased TRIM23 expression is correlated with a poor prognosis in colorectal cancer [321] and lung adenocarcinoma [322].…”
Section: Trimmentioning
confidence: 99%
“…The majority of tumor promoting TRIMs belong to the p53 negative regulatory TRIMs either through an increased polyubiquitination and subsequent proteasomal degradation or, alternatively, by hindering p53 from entering the nucleus and thereby impairing its transcriptional activity. P53 inhibitory TRIM members which are characteristically overexpressed in CRC include TRIM23 [ 58 ], TRIM24 [ 59 ], TRIM25 [ 62 ], TRIM28 [ 67 , 69 ], and TRIM29 [ 70 ]. TRIM23 is significantly overexpressed in CRC, a characteristic associated with poor patient survival.…”
Section: Diverse Oncogenic Signaling Pathways Are Affected By Trimmentioning
confidence: 99%
“…TRIM23 is significantly overexpressed in CRC, a characteristic associated with poor patient survival. Gene set enrichment analysis (GSEA) furthermore revealed that p53 and cell cycle signaling pathways related genes were enriched in patients with high TRIM23 levels [ 58 ]. Mechanistically, TRIM23 promotes proliferation of tumor cells mainly through an augmentation in p53 ubiquitination.…”
Section: Diverse Oncogenic Signaling Pathways Are Affected By Trimmentioning
confidence: 99%
See 1 more Smart Citation